Knowledge And Perception Towards Female Feticide Among Adolescents of Coastal South India - Anjana Ramesh; Darshan Bhagwan; Ramesh Holla; Bhaskaran Unnikrishnan; Rekha Thapar; Prasann Mithra; Nithin Kumar; Vaman Kulkarni (Medsci Publications, 2016)
Introduction: The preference of a male child over a female child has been the main cause for female feticide. The causes can be broadly divided under the grounds of religion, economic and social aspects. Objectives: To assess the awareness and the attitude regarding female feticide among adolescents. Methodology: A cross sectional study was carried at few pre-university colleges in Mangalore. Data was collected using a semi-structured questionnaire. Results: The study included 300 adolescents. 45.7% stated that the major cause for practice of feticide is discrimination between male and female. Majority (62%) of them were aware of all the diagnostic methods to determine the sex of the child and termination methods. 43.3% of the students were aware about the laws enforced. 37% believe that enforcing strict laws could be the way to stop female feticide. Conclusion: Adolescents agreed that the decline in sex ratio is the main impact of female feticide. The students have adequate knowledge about diagnostic methods used for sex determination. They believe that strict law implementation is a promising way to stop female male feticide. However, they were not knowledgeable about the laws enforced for the control.